SIMULATION OF IOT MONITORING OF SOIL MOISTURE AND TEMPERATURE USING ARDUINO UNO ON TINKERCAD USING RULE-BASED ALGORITHMS - Imtiyaz, Muhammad Nidzom; Nabilla, Ferdian Wahyu; Yasin, Moch (STMIK TIME, 2025)
Farmers and plant enthusiasts often face difficulties in maintaining the desired soil moisture level, as manual watering methods are usually ineffective and unstable. Too much or too little water can have a significant impact on plant growth. To resolve this issue, a study was conducted with the aim of designing and testing an automated system capable of monitoring soil moisture and temperature levels. This study adopted a Research and Development (R&D) approach, which was demonstrated in the form of a simulation in Tinkercad. The system was built using an Arduino Uno microcontroller, along with soil moisture and temperature sensors, as well as control logic based on rule-based (if-then) algorithms. Testing showed that this virtual prototype functioned as intended. This system can automatically activate the water pump when the sensor detects dry soil conditions (sensor value < 450) and stop it when the soil is moist or wet. Also, this setup effectively turns on the LED when it gets hotter than what we told it to watch out for (more than 32°C). The data we got tells us that this monitoring setup does its job well and is really good at doing things automatically based on the rules we set, which means it's a great way to solve the problems we have with watering plants by hand.